2014
DOI: 10.3238/arztebl.2014.0273
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Nerve Injuries

Abstract: A thorough knowledge of the anatomy of the vulnerable nerves and of variants in their course can lessen the risk of iatrogenic nerve injury. When such injuries arise, early diagnosis and planning of further management are the main determinants of outcome. If adequate nerve regeneration does not occur, surgical revision should optimally be performed 3 to 4 months after the injury, and 6 months afterward at the latest. On the other hand, if postoperative high resolution ultrasound reveals either complete transec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 27 publications
(22 reference statements)
0
61
0
13
Order By: Relevance
“…Common procedures that may cause nerve injury are osteosynthesis, osteotomy, arthrodesis, lymph node biopsies from the posterior triangle of the neck, carpal tunnel release, Baker's cyst excision, varicose vein surgery and inguinal hernia repair [41].…”
Section: High-risk Surgical Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…Common procedures that may cause nerve injury are osteosynthesis, osteotomy, arthrodesis, lymph node biopsies from the posterior triangle of the neck, carpal tunnel release, Baker's cyst excision, varicose vein surgery and inguinal hernia repair [41].…”
Section: High-risk Surgical Proceduresmentioning
confidence: 99%
“…A study reported that the most common surgical interventions associated with peripheral nerve injury are as follows in decreasing order: 45% major procedures (orthopaedic procedures, abdominal surgery and trauma), 27% minor procedures (lymph node surgery and varicose vein surgery), 15% neurosurgical interventions (carpal tunnel operations and tenolysis), and 4% non-surgical interventions (arterial or venous puncture and plaster cast) [36,41].…”
Section: High-risk Surgical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations